Actin‐bundling protein plastin 3 is a regulator of ectoplasmic specialization dynamics during spermatogenesis in the rat testis. Issue 9 (5th June 2015) - Li, Nan; Mruk, Dolores D.; Wong, Chris K. C.; Lee, Will M.; Han, Daishu; Cheng, C. Yan
ABSTRACT: Ectoplasmic specialization (ES) is an actinrich adherens junction in the seminiferous epithelium of adult mammalian testes. ES is restricted to the Sertoli‐spermatid (apical ES) interface, as well as the Sertoli cell‐cell (basal ES) interface at the blood‐testis barrier (BTB). ES is typified by the presence of an array of bundles of actin microfilaments near the Sertoli cell plasma membrane. These actin microfilament bundles require rapid debundling to convert them from a bundled to branched/unbundled configuration and vice versa to confer plasticity to support the transport of 1) spermatids in the adluminal compartment and 2) preleptotene spermatocytes at the BTB while maintaining cell adhesion. Plastin 3 is one of the plastin family members abundantly found in yeast, plant and animal cells that confers actin microfilaments their bundled configuration. Herein, plastin 3 was shown to be a component of the apical and basal ES in the rat testis, displaying spatiotemporal expression during the epithelial cycle. A knockdown (KD) of plastin 3 in Sertoli cells by RNA interference using an in vitro model to study BTB function showed that a transient loss of plastin 3 perturbed the Sertoli cell tight junction‐permeability barrier, mediated by changes in the localization of basal ES proteins N‐cadherin and β‐catenin. More importantly, these changes were the result of an alteration of the actin microfilaments, converting from their bundled to branched configuration when examined microscopically, and validated by biochemical assays that quantified actin‐bundling and polymerization activity. Moreover, these changes were confirmed by studies in vivo by plastin 3 KD in the testis in which mis‐localization of N‐cadherin and β‐catenin was also detected at the BTB, concomitant with defects in the transport of spermatids and phagosomes and a disruption of cell adhesion most notably in elongated spermatids due to a loss of actin‐bundling capability at the apical ES, which in turn affected localization of adhesion protein complexes at the site. In summary, plastin 3 is a regulator of actin microfilament bundles at the ES in which it dictates the configuration of the filamentous actin network by assuming either a bundled or unbundled/branched configuration via changes in its spatiotemporal expression during the epithelial cycle.—Li, N., Mruk, D. D., Wong, C. K. C., Lee, W. M., Han, D., Cheng, C. Y. Actinbundling protein plastin 3 is a regulator of ectoplasmic specialization dynamics during spermatogenesis in the rat testis. FASEB J. 29, 3788‐3805 (2015). www.fasebj.org